Planktonic copepods from coastal and inshore waters of Tudor Creek, Mombasa. - Okemwa, E.N. & N. Revis (Kenya Journal of Sciences, Series B, Biological Sciences, 1986)
Fifty two free swimming planktonic copepod species were identified from the samples collected from three stations in Tudor Creek. This appears to be the first systematic account of copepods reported from the coastal and inshore waters of Kenya.
Available in Wilson Copepod Library (non-digital)